Isolation and syn Elimination of a Peterson Adduct to Obtain Optically Pure Product in the Diastereoselective Synthesis of Oxazolidinone- Functionalized Enecarbamates - Solomon, Marissa R.; Saito, Hideaki; Sivaguru, J.; Jockusch, Steffen; Inoue, Yoshihisa; Adam, Waldemar; Turro, Nicholas J. (Letters in Organic Chemistry, 2009)
The Peterson reaction of (4R)-N-(trimethylsilyl)methyl-4-alkyloxazolidin-2-one gives (E/Z)-(4R)-N-(2',3'- diphenylbut-1'-enyl)-4-alkyloxazolidin-2-ones (enecarbamates) with increasing (Z)-selectivity and moderate-to-high diastereoselectivity in the individual E isomer as a function of increasing temperature. X-ray structure of the Peterson adduct, (4R,3'S)-N-(2',3'-diphenyl-2'-hydroxy-but-1'-enyl)-4-alkyloxazolidin-2-one (enecarbamates), reveals the rationale for the formation of a single isomer through syn elimination. The optically pure enecarbamates obtained with the Peterson adduct were further employed for photochemical and photophysical studies.
Keywords: asymmetric synthesis